Critical thinking as a necessity for social science students capacity development: How it can be strengthened through project based learning at university - Witarsa,; Muhammad, Syahril (Frontiers in Education, 2023)
Critical thinking is necessary for students because it empowers them to solve problems, especially during the learning stage and in real-life situations within society. Based on this fact, the present study proposes a citizenship project model that aims to enhance the Elementary School Teacher Education Study Program by emphasizing critical thinking among students during the teaching of Civic Education at universities in Indonesia. The research is of the experimental quasi-research type, which comprises two classes: an experimental class and a control class. Both the classes were conducted to compare the effectiveness of the proposed citizenship project learning model. The statistical package for the social sciences was used for data analysis. To attain the required results on the implementation of the citizenship project learning model, there were several stages, including problem identification, problem formulation, information gathering, documenting the process, showcasing the results, and reflective analysis of the model implementation process. The results have revealed a significant improvement in the critical thinking abilities of the students in the experimental class category compared to the control-class category. Thus, it is concluded that the adoption of a citizenship project learning model is appropriate for critical thinking skills' improvement of students taking up citizenship education study programs at universities.